Chemical Evaluation of Lignocellulolytic Microbes, Yeast and Lactobacilli Addition to Rice Straw at Silage Preservation - L. M. Yusiati; Z. Bachrudin; Kustono (Kustono); D. Rahmadi (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy